PENGARUH DER, ROA DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PT HANJAYA MANDALA SAMPOERNA TBK PERIODE TAHUN 2013 - 2022 - Wulandari; Aria Aji Priyanto (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of capital DER, ROA and company size on firm value. The type of research used in this research is descriptive quantitative research. The type of data used in this study is secondary data. The data source used in this study is the financial statements of the company PT Hanjaya Mandala Sampoerna Tbk for the period 2013-2022. The population in this study amounted to 1 company. The sampling technique in this study used the financial statements of PT. Hanjaya Mandala Sampoerna Tbk. Data analysis techniques using descriptive statistical analysis, classical assumption tests (normality test, multicolonierity test, heteroscedasticity test, and autocorrelation test), multiple linear regression analysis and hypothesis testing (T test, F test), and coefficient of determination. DER significance value is 0.01, meaning the value is smaller than 0.05, while the t-test results are greater than the table value, namely 6.260 > 2.365, so it can be said that H1 is accepted. that the ROA significance value is 0.679, meaning the value is greater than 0.05 while the t-test results are smaller than the table value -0.435 < 2.365 so it can be said that H2 is rejected. The significance value of company size is 0.000, meaning the value is smaller than 0.05, while the t-test results are greater than the table value -8.814 > 2.365, so the hypothesis is accepted. The Fcount value is greater than the Ftable value, namely 69.497 > 4.76, so it can be said that H4 is accepted and has a significant value of 0.000 which is smaller than the significance level, namely 0.000 < 0.05, so the hypothesis is accepted. The results of this study indicate that capital structure partially has significant effect on firm value, profitability partially has no significant effect on firm value, company size partially hassignificant effect on firm value and DER, ROA and company size simultaneously affect firm value.